Application Of The Project-Based Learning Model To Improve Learning Outcomes In Sports Psychology College Using The "Experiential Learning" Method - Grafitte Decheline; atri widowati; sugih suhartini; Qory Jumrotul ‘Aqobah; Sri Murniati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The implementation of the Project Based Learning (PjBL) model has now become a learning model that is popular among both teachers and lecturers. The PjBL concept provides space for students to be more active in learning and continuously improve the effectiveness of learning at school. Using the PjBL model, the problems that arise are how to increase students' understanding in sports psychology courses using the experiential learning method, and what are the student learning outcomes in sports psychology courses using the PjBL learning method. Experiential Learning uses Kolb's Experiential Learning Cycle in its scope of the Project Based Learning model which also uses the PTK Kemmis and MC Taggart models to sort out the steps and stages of the learning presented. This research was applied to 38 students in the Sports Psychology Course in Class D. Kemmis and Taggart's Classroom Action Research (PTK) model uses 2 cycles starting from Analysis, Reflection, Action and Observation to the final step, Evaluation. The results of Cycle I, as many as 22 people (57%) completed, the rest did not meet the completion standards. After reflection was carried out, Cycle II was carried out based on the results of cycle I reflection, so that as many as 35 people out of 38 students or 92% of students completed it. Based on the research that has been carried out, there is an increase of 35% from cycle I to cycle II based on reflections carried out and comprehensive evaluations from lecturers and students.